IMPLEMENTASI E-MODULE BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN MATERI BUDAYA LOKAL PESERTA DIDIK KELAS IV SD - Niniss Margareth; Erni Suharini; Eko Handoyo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to implement and determine the effectiveness of Project Based Learning (PjBL)-based e-modules in improving fourth-grade students' understanding of local culture at SDN Cangkuang Elementary School. The study used a mixed methods approach with a concurrent embedded model, which combines quantitative and qualitative data simultaneously. There were 12 students participating in the study. Data collection techniques were carried out through pretest-posttest tests and observations. The research instruments consisted of pretest and posttest sheets for material comprehension and observation sheets for learning activities. Quantitative data analysis was performed using descriptive statistics using SPSS and N-Gain calculations, while qualitative data was analyzed using descriptive narrative analysis. The results showed that the average N-Gain value was 0.56 or 56.25%, which was in the moderate improvement category. In addition, the observation results showed that students were more active, enthusiastic, and involved in project-based learning activities. Thus, it can be concluded that the Project Based Learning-based e-module is effective in improving elementary school students' understanding of local culture.